THE MANIFESTATION OF UBERMENSCH AND DER WILLE ZUR MACHT (WILL TO POWER) IN CHAIRIL ANWAR’S FOUR POEMS - TETUKO, KURNIA WIDHI (Jurnal Ilmiah Mahasiswa FIB, 2013)
The issue of Existentialism in literary work has become interesting topic to discuss since the late of 1800’s till nowadays. This phenomenal thought led to the new era of philosophical thought, as many philosophers called post modernism. The idea of "God is Dead (Gott ist tot)" introduced by Nietzsche has changed all the mindsets of western people at that time to find the new "faith", value, and morality.The Ubermensch born as the Overman or Superman that can handle and answer the death of God. They (the Ubermensch) are those who are brave to challenge the death, they love challenge and short time of peace to measure their best potential. Nietzsche explained that Ubermensch is the combination of three characters: strength, cleverness, and pride. Ubermensch also has four aspects: Gott ist tot (God is dead), the spirit to gain the power and authority, bravery to challenge the death, and trans valuation moral. Meanwhile, one of the manifestations of Ubermensch concept is Der Wille Zur Macht (Will to Power). Nietzsche himself adores art as his sublimation to manifest his Ubermensch. It can be proven by his work entitled "The Birth of Tragedy". The idea of Ubermensch and Will to Power according to writer’s interpretation has influenced Chairil Anwar "as the famous Indonesian poet" to make the poem that manifest the idea of Ubermensch and Will to Power.This study uses qualitative approach in relation to the use of clear and systematic description about the phenomenon being studied. The intrinsic and extrinsic elements of the poems are used by the writer to reveal the manifestation of Ubermensch and Will to Power in Chairil Anwar’s four poems.By analyzing the intrinsic and extrinsic element of the poems, the writer reveals the manifestation of Ubermensch in Chairil Anwar’s selected poems. They are "Aku", "Kerawang Bekasi", "Prajurit Jaga Malam", and "Maju". The manifestation of Ubermensch shows the aspect of "Bravery to Challenge the Death and the manifestation of Will to Power"Keywords : Existentialism, Ubermensch, Will to Power, Chairil Anwar’s Four Poems.